THE RSEZ SUSTAINABLE DEVELOPMENT NECESSITY DRIVEN PUBLIC RELATION MODEL-AN INSTRUMENT FOR ENVIROMENT REGULATION AND MANAGEMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Sustainable development supposes harmonic development o f all spheres - in ecological, economic, social areas - and is aimed at satisfaction of society’s both existing and future needs. Company “Rezekne Special Economic Zone" (RSEZ) is established to endorse development o f favorable business environment. RSEZ’s recommendations for production and services development proposes use o f various existing local resources that would lead to sustainable development in the Rezekne region. However successful accomplishment of development propositions is possible if it is supported by effective corporate communications within RSEZ organizational environment. An article provides analysis o f main elements of RSEZ organizational environment and proposes PR (public relations) actions to promote organizational communications with target audiences.